Representation of the elderly in trials of laparoscopic surgery for colorectal cancer. (December 2014) - Schiphorst, A. H. W.; Pronk, A.; Borel Rinkes, I. H. M.; Hamaker, M. E.
Abstract Aim Most patients with colorectal cancer are elderly, but there are few data on the optimal surgical treatment for this age group and most studies are observational. We have reviewed the characteristics of randomized trials reporting laparoscopic surgery for colorectal cancer to determine the degree to which the elderly are represented. Method A search was conducted of the NIH clinical trial registry and the ISRCTN register for randomized trials on laparoscopic surgery for colorectal cancer. Trial characteristics and end‐points were extracted from the registry website and supplemented by published results where available. Results Of 52 trial protocols the majority did not state any restrictions regarding cardiac [40 (77%)] or pulmonary function [41 (79%)]. More than half [30 (58%)] had no restrictions regarding American Society of Anesthesiologists score. Twenty‐three (44%) trials excluded the elderly either simply on age or by comorbidity or organ function. When an upper age limit was set, half of the studies had no restriction regarding organ function, indicating that chronological age rather than physical condition was taken as the reason for exclusion. In 45 (86%) of the trials the average age of participants was < 70 years, and no details of concurrent disease were given. Conclusion Participation of the elderly in trials of laparoscopic surgery for colorectal cancer is very limited. This should be remedied in future trials if adequate information on the majority of patients with colorectal cancer is to be obtained.